Long‐term changes in spatially coherent extreme precipitation systems over Central India - Anu Gupta; Hiroshi G. Takahashi (Atmospheric Science Letters, 2022)
Abstract The present study examined extreme rainfall events (EREs) in central India during the summer monsoon season, focusing on their spatial characteristics. A station‐based gridded and a station‐satellite‐blended dataset was used to examine long‐term and recent variations in precipitation characteristics for 50 years (1951–2000) and 38 years (1981–2018), respectively. A precipitation system approach (PSA) was applied to identify the ERE precipitation systems and categorized spatial sizes of ERE systems into three categories: sporadic, intermediate, and massive ERE precipitation systems. Conventionally, the ERE frequency is equal to the total number of ERE grids, whereas PSA counts ERE systems. The sporadic precipitation grid contributes 42% of all the ERE grids, and sporadic EREs frequency increases in the long‐term. The long‐term trend of intermediate and massive EREs does not increase and quite sharply increases, respectively, and these EREs are also intensifying. Recent 38 years have shown a reverse in the trends of ERE characteristics, the frequency and intensity of intermediate and massive EREs have decreased, whereas the massive ERE systems are broadening.